GC-MS Analysis of Essential Oil of Artemisia Annua and Biological Activities of its Extracts - Kawra, Monika; Sakshi; Saklani, Sarla; Bishoyi, Arun Kumar (SCHOOL SCIENCE, 2025)
Medicinal plants form the basis of healthcare in many societies. Approximately 80 per cent of traditional medicines used in primary healthcare are of indigenous origin. Uttarakhand Himalayas are considered to be a rich source of important medicinal and aromatic plants. Traditionally, medicinal plants are used by the local people to obtain health benefits. Artemisia annua is a wild growing aromatic plant known for its anti-malarial activity and an array of secondary metabolites. The present study was performed to investigate the chemical composition, antioxidant and antimicrobial activity of essential oil and different extracts of A. annua. The essential oil was analysed by GC-MS (Gas chromatography– mass spectrometry) and has shown thirty-seven components. The result found that this plant can be a useful raw material for development of nutraceutical agent due to the presence of various secondary metabolites. The extracts possessed significant antioxidant and antimicrobial activity and thus, can be utilised as a nutraceutical agent.